l-lactate kinetics after abdominal aortic surgery and intestinal ischemia - An observational cohort study - Novotný, Tomáš; Staffa, Robert; Tomandl, Josef; Krivka, Tomas; Slaby, Ondrej; Kubicek, Lubos; Biros, Ernest; Tomandlova, Marie; Vlachovsky, Robert; Sponiar, Jan; Radova, Lenka; Konieczna, Anna (International journal of surgery, 2022)
BACKGROUND: Postoperative intestinal ischemia is a severe complication in abdominal aortic surgery. Early diagnosis is needed for adequate and timely treatment. We studied the postoperative kinetics of l-lactate in vascular patients to assess its value as a marker for early postoperative intestinal ischemia detection. MATERIAL AND METHODS: We performed a prospective non-randomized single-center observational cohort study in eighty elective patients, fifty operated on for abdominal aortic aneurysm (AAA) and thirty for aortoiliac occlusive disease (AIOD). Serum l-lactate was measured preoperatively, intraoperatively, and postoperatively at defined timepoints up to postoperative day 7. Intestinal ischemia was detected using MRI enterocolography. We have used univariate logistic regression and receiver operating characteristics curves for the evaluation of marker accuracy. RESULTS: We recorded 6 cases of postoperative intestinal ischemia (7.5%), five non-transmural and one transmural. Two patients died because of this complication (mortality 33%). The comparison of AAA and AIOD cohorts showed a significant difference in l-lactate levels at one intraoperative timepoint, which was attributable to procedure differences. The only preoperative factor associated with higher l-lactate levels at some timepoints was chronic kidney disease. Patients suffering postoperative intestinal ischemia had elevated serum l-lactate levels at multiple timepoints. The most accurate timepoint for diagnosis was 24 h after the declamping of the vascular reconstruction (DC24H), the second was 10 min after declamping. Sensitivity, specificity, positive and negative predictive values at timepoint DC24H were 100%, 82%, 32%, and 100%, respectively. CONCLUSION: Serum l-lactate levels might help in the early detection of postoperative intestinal ischemia after aortic surgery if proper timepoints are used. Cutoff values need to be established in large-scale prospective studies.
Keywords: Humans; Ischemia; lidé; ischemie; Kinetics; aneurysma břišní aorty; laktáty; prospektivní studie; Postoperative Complications; Lactates; Prospective Studies; pooperační komplikace; kinetika; Aortic Aneurysm, Abdominal